A High-Level Language for Rule-Based Modelling - Pedersen, Michael; Phillips, Andrew; Plotkin, Gordon D. (PLoS ONE, 2015)
Rule-based languages such as Kappa excel in their support for handling the combinatorial complexities prevalent in many biological systems, including signalling pathways. But Kappa provides little structure for organising rules, and large models can therefore be hard to read and maintain. This paper introduces a high-level, modular extension of Kappa called LBS-Kappa. We demonstrate the constructs of the language through examples and three case studies: a chemotaxis switch ring, a MAPK cascade, and an insulin signalling pathway. We then provide a formal definition of LBS-Kappa through an abstract syntax and a translation to plain Kappa. The translation is implemented in a compiler tool which is available as a web application. We finally demonstrate how to increase the expressivity of LBS-Kappa through embedded scripts in a general-purpose programming language, a technique which we view as generally applicable to other domain specific languages.